Pengendalian Alternatif Hama Serangga Sayuran dengan Menggunakan Warna sebagai Perangkap Mekanis - Lukmanul Hakim; Erdi Surya; Abdul Muis (Serambi Saintia : Jurnal Sains dan Aplikasi, 2017)
This study aimed to test a two models of trap insects, which are made from paper media trap color and light color. The color of tested is red, yellow, and green, while the colored light consisting of light red, yellow, and green. This study was conducted from July to August 2016. This study was conducted at the experimental garden "Hight School Vocational Agricultural Development” Seulawah Valley Districts, Large Districts of Aceh, Aceh Province. Object of research is a corn plant. Method research approach RCBD with 3 treatments and 4 replications. Variable observation insect populations trapped on paper media color and light color. The results showed the highest insect population on paper and light yellow color, the population was on the green paper and the lowest population encountered on red paper. Key word : alternative control, mechanical traps, vegetable.